Probing the mechanism of xanthine oxidase and 2-amino xanthine: an implication of energy, charge bond order and wave function. - Bitew, Mamaru (International Journal of Advanced Chemistry, 2018)
Xanthine oxidase (XO) is an important molybdenum-containing enzyme catalyzing the hydroxylation of hypoxanthine to xanthine and xanthine to uricacid. The mechanistic action by which xanthine oxidase oxidizes purine derivatives is not well understood. A better understanding of the overall mechanism is supposed to enhance our ability to control the metabolic properties of potential drug molecules metabolized by this enzyme. In this work a model substrate, 2-Amino Xanthine has been used to study the mechanistic action of the enzyme. For this reason, the present theoretical work was intended to probe a unified mechanism for the oxidation of 2-Amino Xanthine by xanthine oxidase. Parameters like total electronic energy, Mulliken atomic charges, wave functions, and percent contribution of chemical fragments were generated using a DFT method employing B3LYP level of theory with 6-31G(d',p') basis set for nonmetals and LanL2DZ basis set for molybdenum. AOmix software package that employs single point energy output as an input file was employed for wave function and percent fragment analysis. From these result new reaction intermediates and plausible reaction mechanism root has been reported for reductive and oxidative half reaction using 2-Amino Xanthine as model substrate. In this work it can be concluded that a stepwise mechanistic route with hydrogen bonding reaction complex and active site resemble very rapid Mo (V) intermediate is most plausible.